Settler Bolsheviks in the Soviet “Eastern” - Morrison, A (Routledge, 2020)
The Revolutionary and Civil War period in Central Asia became a popular subject for novels and films in the USSR, portraying Russians as the main agents of progress in Central Asia against the villainous Basmachi, bandits who resisted the new Soviet order. In the 1960s these stories developed into a hugely popular genre of film, the Soviet “Eastern” that was strongly influenced by American “Westerns,” with the Basmachi playing the role of American Indians, and Bolshevik commissars and soldiers the cowboys and cavalry. This paper will explore the extent to which Soviet Easterns reflect settler colonial narratives, and the degree to which the Bolshevik claim to be bringing enlightenment and progress to a backward region has commonalities with settler colonialism elsewhere. It will focus on Semirechie, the main Russian settler colony in southern Central Asia, and in particular the film Alye Maki Issyk-Kulya (The Scarlet Poppies of Issyk-Kul, Bolotbek Shamshiev, 1972) and the novel on which it was based, Alexander Sytin’s Kontrabandisty Tian’-Shanya (The Smugglers of the Tian-Shan, 1930). It argues that while Sytin’s writing certainly does touch on settler colonial themes, these are muted in the film, which is instead suffused with Kyrgyz national narratives and symbolism.